ANALYSIS OF COMMUNITY PARTICIPATION LEVEL IN THE MANAGEMENT OF VILLAGE OWNED BUSINESS ENTITIES (BUMDES) IN KADING VILLAGE, SUB-DISTRICT TANETE RIAJA, BARRU REGENCY - Adrianah; Samsibar; Asmillah, Nur (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 The Visual journal